The Effect of the Simulation Method on Creative Thinking Ability and Basic Teaching Ability of Islamic Religious Education Students - Hamzah, Hamzah; Nur’aini, Nur’aini (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
This study aims to determine the effect of the simulation method on the ability to think creatively and the basic teaching skills of students majoring in Islamic Religious Education (PAI) at the Ibnu Sina High School-Batam. The approach used in this research is quantitative, using quasi-experimental techniques. The research design used is the pretest and posttest design. The sample used in the study was students majoring in PAI, totaling 23 people who took the Learning Methods and Strategies course. Data collection is done by testing techniques. The test is used to measure students' creative thinking skills and basic teaching abilities. Data were analyzed using the N-gain and correlation test and F test, in this case, it was done with the help of SPSS 16 software. Based on the data and analysis results and statistical tests (N-gain test) it can be concluded that the simulation method has an effect on the ability to think creatively by 56 % and the basic ability to teach students majoring in Islamic Religious Education (PAI) at the Ibnu Sina High School-Batam is 79%. Based on the F test, these results are in the very convincing category. Therefore it can be said that the simulation method can be used as an alternative to developing students' creative thinking skills while improving their basic teaching skills.